Perceived Family Functioning Profile in Adolescents at Clinical High Risk for Psychosis: Rigidity as a Possible Preventive Target - Iorio, Melanie; Casini, Erica; Damiani, Stefano; Fusar-Poli, Paolo; Borgatti, Renato; Mensi, Martina Maria; , Clinical High Risk State for Psychosis Research Group (Frontiers in Psychiatry, 2022)
The presence of a positive family relationship has been suggested as a protective factor from parental stress and from the development of full-blown psychosis. However, to date, there is limited research on family functioning in adolescents with psychosis and at clinical high risk for psychosis (CHR-P). This study is aimed at comparing family functioning and perceived stress in parents of adolescents with either CHR-P, early onset psychosis (EOP), or other psychiatric disorders (no CHR-P). As a secondary aim, it will correlate family functioning with parental perceived stress in order to find critical targets of intervention. We conducted a Reporting of Studies Conducted Using Observational Routinely-Collected Health Data (RECORD)—compliant, real-world, cross-sectional study. One-hundred and eleven adolescents aged 12–17 who access the institute of hospitalization and care with scientific character (IRCCS) Mondino Foundation Neuropsychiatric services (Pavia, Italy) between 2017 and 2020 and their parents (n = 222) were included. Sociodemographic characteristics of adolescents and their parents were collected. Family functioning was evaluated through the Family Adaptability and Cohesion Evaluation Scale-IV (FACES-IV) and the level of stress through the Perceived Stress Scale (PSS). Twenty adolescents had EOP, 38 had CHR-P, and 59 had no CHR-P. In total, 2.6% of CHR-P adolescents were adopted, 76.3% had separated-divorced parents, and 34.2% of parents had a depressive disorder. Among the FACES-IV sub-scale, maternal rigidity was progressively increased from no-CHR-P to CHR-P to EOP group, with statistical differences between EOP and the other two groups (p = 0.01). CHR-P mothers and fathers showed a high level of PSS values, without group difference. Lastly, PSS values correlated positively with the Rigidity, Disengagement, and Chaos scale of FACES-IV and negatively with the Communication scale (p < 0.05). Our results suggest that family functioning has a central role and could represent a worthwhile target of intervention for adolescents at CHR-P, leading the way to new preventive approaches.